Web-Based E-Office System Design Using Yii2 Framework - Siswanto, Hery; Shofiyatun, Siti (Universitas Muhammadiyah Yogyakarta, 2025)
Universitas Muhammadiyah PKU Surakarta in its efforts to improve the efficiency and effectiveness of office administration management faces challenges in document management and workflows that are still running conventionally. Manual processes often take longer, are prone to errors, and require large physical storage space. To overcome these problems, this study aims to design and build a web-based E-Office system by utilizing the Yii2 framework. The method used in this study is SDLC and the system design used includes the needs analysis stage, system design using the Unified Modeling Language (UML) consisting of use case diagrams, activity diagrams, and class diagrams, and system implementation using the Yii2 framework with the PHP programming language and MySQL database. Implementation using Devops. The Yii2 framework was chosen because of its robust structure, complete security features, SSO login with Google, and its ability to accelerate the application development process. The E-Office system developed will include various essential features such as incoming and outgoing mail management, electronic mail disposition, SPPS management, and document status tracking features. It is expected that with the implementation of this system, Muhammadiyah University of PKU Surakarta can realize a more modern, paperless, transparent, accountable office administration system, and is able to increase productivity and quality of service for all academicians. This system is also expected to facilitate the decision-making process of leaders through fast and accurate access to information.